Estudo de interação genótipo x ambiente para peso e perímetro escrotal à desmama na raça Canchim - Carvalho, Fábio Menezes de (2007)
In beef cattle genetic evaluation programs, the existence of genotype x environment interaction is of special interest when merit of the animals depends on the environment they are evaluated, that is, when a genotype is superior in one environment but not in others. The objective in this study was to evaluate the existence of genotype x environment interaction for weight (WW) and scrotal circumference (SC) at weaning in Canchim cattle, using data belonging to herds from Southeast and Mid West regions of Brazil. Herds were grouped according to two criteria: (1) by geographical region, considering animals born in Southeast and Mid West regions of Brazil; (2) by homogeneous production regions, considering only animals born in the State of São Paulo. Data on 29,367 WW and 8,800 SC were used for analyses in criterion 1, and 15,041 WW for analyses in criterion 2. The region in which the calf was born and raised was considered as the environment, and two methods were used to evaluate the interaction by both criteria. In method 1, genetic correlation between the same trait among the environments, in two (criterion 1) and three-trait (criterion 2) analyses, was estimated, considering the trait in each region as a different trait, using the derivative free restricted maximum likelihood method, with a statistical model which included the fixed effects of contemporary group (breeder-owner-year and season of birth-sex-genetic group of dam-feeding regime) and the covariates age of dam (linear and quadratic effects) and age of calf (linear effect; only for SC), and the additive direct and maternal, permanent environmental and residual random effects. Spearman rank correlations for breeding values of bulls in different regions were also calculated. In method 2, for both criteria, one-trait analyses using two similar models were done, but one with and the other without the uncorrelated sire-region random effect, and the difference between them was tested by the likelihood ratio test. In criterion 1, the genetic correlations between WW and SC in Southeast and Mid West regions were equal to 0.78 and 0.97, respectively, while in criterion 2, the genetic correlations between WW in West of São Paulo - Paraná and Araraquara regions, West of São Paulo - Paraná and Leiteira regions, and Araraquara and Leiteira regions were 0.87, 0.69 and 0.76, respectively. The rank of bulls according to their breeding values changed from one region to the others, and the models with and without sire-region effect were different, for all traits. These results suggest the existence of genotype x environment interaction for the traits in the studied population.